Bioethical approximations to the case of Charlie Gard - Salgado-Fernández, Horacio (Acta Bioethica, 2019)
The litigation that confronted the parents of the child Charlie Gard against the Great Ormond Street Hospital in London, first, and against the United Kingdom itself, later, generated media effects worldwide but little debate from a bioethical perspective. This article summarizes some relevant aspects of the controversy that allow analyzing three of the lessons formulated by Wilkinson and Savulescu in this regard. Two bioethical reflections are also proposed: the first in relation to the difficulty in the application of principles to examine the case, and the second referred to the interdisciplinarity required for its analysis.